2022
DOI: 10.1038/s41598-022-24460-7
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation electrodynamics of superinsulators

Abstract: Superinsulators offer a unique laboratory realizing strong interaction phenomena like confinement and asymptotic freedom in quantum materials. Recent experiments evidenced that superinsulators are the mirror-twins of superconductors with reversed electric and magnetic field effects. Cooper pairs and Cooper holes in the superinsulator are confined into neutral electric pions by electric strings, with the Cooper pairs playing the role of quarks. Here we report the non-equilibrium relaxation of the electric pions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Superinsulators [17,[36][37][38][39], with their divergent electrical resistance, have been experimentally detected in InO [40], TiN [36], NbTiN [41], and NbSi [42]. A recent measurement of the dynamic response of superinsulators confirmed that the potential holding together ± charges is indeed linear [43].…”
Section: Adding Quantum Phase Slipsmentioning
confidence: 96%
“…Superinsulators [17,[36][37][38][39], with their divergent electrical resistance, have been experimentally detected in InO [40], TiN [36], NbTiN [41], and NbSi [42]. A recent measurement of the dynamic response of superinsulators confirmed that the potential holding together ± charges is indeed linear [43].…”
Section: Adding Quantum Phase Slipsmentioning
confidence: 96%
“…They were first theoretically predicted in [5], while the final form of the theory describing this new state of matter was established in [7]. Superinsulators have been experimentally detected [8][9][10][11][12][13][14] in thin superconducting films, which, close to the SIT, have an emergent granularity and behave as a self-organized JJA.…”
Section: Introductionmentioning
confidence: 99%
“…They were first theoretically predicted in [5], while the final form of the theory describing this new state of matter was established in [7]. Superinsulators have, than, been experimentally found in [8][9][10][11][12][13][14] in thin superconducting films which, close to the SIT, have an emergent granularity and behave as a self organized JJA.…”
Section: Introductionmentioning
confidence: 99%